Interest and motivation of students on traditional prose teaching in Malay language literature components - Zainal Abidin, Noorzailiza; Said, Rozita @ Radhiah; Md Sabil, Azhar (Human Resource Management Academic Research Society, 2018)
Nurturing human capital with a sense of pride in Malay Language and literature requires good determination and delivery. This study aimed to identify students' interest and motivation towards the teaching and learning of the Malay literary component of the traditional prose genre as well as to identify the level of teaching of Malay teachers according to the students' perceptions. A total of 50 Form 2 students in a secondary school of Gemas, Negeri Sembilan were randomly selected as sample by various ethnic groups and achievement levels. This study was a survey, in which the data were collected through questionnaires consisting of 32 items. The data collected were analyzed descriptively using SPSS version 21. The findings showed that the level of interest and motivation of the students towards the traditional prose genre was low and the traditional method of teaching caused the respondents not interested in studying this classic Malay literature. Therefore, the Malay Language teachers should not only strengthen themselves in pedagogy but also inspire the creativity to make the teaching and learning sessions fun that attract the students to be more motivated to absorb the knowledge acquired for their lifetime needs.